2008
DOI: 10.1038/ja.2008.52
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Potent in Vitro Antitrypanosomal Activities of Ten Microbial Metabolites

Abstract: More than 400 compounds isolated from soil microorganisms, and catalogued in the antibiotic library of the Kitasato Institute for Life Sciences, were screened against African trypanosomes. Ten compounds were found to have selective and potent antitrypanosomal activity in vitro: aureothin, cellocidin, destomycin A, echinomycin, hedamycin, irumamycin, LL-Z 1272b , Omethylnanaomycin A, venturicidin A and virustomycin A. Results of the in vitro assays using the GUTat 3.1 strain of Trypanosomal brucei brucei and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 32 publications
0
71
1
Order By: Relevance
“…18 This strain, donated by Dr Y Yabu (Nagoya City University, Japan), is a clone derivative of a stock EVE (Edinburgh Veterinary Expedition) 10 that was originally isolated in 1966 from a naturally infected bovine in Uganda. Isolation of macrotetrolides from the culture broth of Streptomyces sp.…”
Section: Antitrypanosomal Activity In Vitromentioning
confidence: 99%
“…18 This strain, donated by Dr Y Yabu (Nagoya City University, Japan), is a clone derivative of a stock EVE (Edinburgh Veterinary Expedition) 10 that was originally isolated in 1966 from a naturally infected bovine in Uganda. Isolation of macrotetrolides from the culture broth of Streptomyces sp.…”
Section: Antitrypanosomal Activity In Vitromentioning
confidence: 99%
“…6,7 Animals Female CD1 mice (ICR), 20-25 g, were obtained from Charles River Japan Inc. (Kanagawa, Japan). Animals were placed in groups of four per cage, kept in a room under negative pressure with flow of 0.1-0.2 m sec À1 .…”
Section: Trypanosomesmentioning
confidence: 99%
“…6,7 We have discovered a further three peptide antibiotics, leucinostatin A and B (produced by soil fungi, Paecilomyces sp.) and alamethicin I and tsushimycin (from the antibiotic library) (Figure 1), which show potent or moderate antitrypanosomal properties.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported various microbial metabolites exhibiting potent antimalarial [1][2][3][4] and antitrypanosomal properties. [5][6][7] We have recently found that the known 20-membered ring macrodiolide antibiotics, the bispolides, 8 together with new derivatives, exhibit selective antitrypanosomal and potent antimalarial activities, both in vitro and in vivo. Here, we report the antitrypanosomal and antimalarial profiles of bispolides, their derivatives ( Figure 1) and the related 16-membered ring macrodiolide antibiotic as elaiophylin (azalomycin B) 9,10 (Figure 1) in comparison with those of clinically used antitrypanosomal drugs, such as suramin and eflornithine, and two clinically used antimalarial drugs, artemisinin and chloroquine.…”
mentioning
confidence: 99%
“…The 13,13¢-dimethoxy compound, bispolide A3, prepared from bispolide A1 by reaction with 0.04%-HCl in MeOH, was reduced by NaBH 3 In vitro antiprotozoal activities against Trypanosoma brucei brucei strain GUTat 3.1, Plasmodium falciparum strains K1 (drugresistant) and FCR3 (drug-sensitive), and cytotoxicity against human diploid embryonic cell line MRC-5 were measured as described previously. 1, 5 In vivo antitrypanosomal activity for T. b. brucei strain S427 was measured as described previously. 6 Test compounds were solubilized in an aqueous mixture of 10% DMSO-Tween 80 and EtOH (7:3) and administered i.p.…”
mentioning
confidence: 99%